INOCULAÇÃO DE BACTÉRIAS SOLUBILIZADORAS DE FOSFATO EM PASTAGEM - TENÓRIO, Kamila de Paula; ROCHETTI, Ana Carolina Alves; DEZAN, Íris Mendes Namizaki; PUPIM, Gabriel de Souza; CUNHA, Júlia Souza Pires; NOGUEIRA, Lavínia Rodrigues (ANAIS DO ENIC, 2025)
-